Cost Analysis of Improving Urban Railway Services on Arjonegoro Commuter - Setyarini, Ika Oktavia; Wulandari, Esti; Patriadi, Andi (Publica Scientific Solution, 2025)
Improvement of train services will always develop along with the development of passenger demand. Likewise in the case of Arjonegoro Train as one of the mainstay urban trains in East Java. The development of local trains, especially Arjonegoro Train, triggers the public's desire to get optimal service. The increasing expectations of passengers can be the basis for planning to improve train services. However, every improvement plan also requires a mature budget and cost design so that the plan can be implemented properly. The data used in this study are primary and secondary data. 199 respondents were successfully obtained as primary data. This study uses descriptive analysis methods and literature studies in determining the service improvements needed and the cost of improving these services will be estimated. This study will examine the level of passenger satisfaction with 6 service variables to determine what services need to be improved from Arjonegoro Train. The results of the study showed that the service with the highest negative sentiment was in the availability of seats, availability of travel schedules, availability of platforms and availability of canopies. This can be mitigated by improving services in the form of adding 1 Trainset and improving the platform and canopy at the station with an estimated cost requirement for improving the Arjonegoro train service of Rp. 110,373,211,939.